2003
DOI: 10.1515/cclm.2003.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Polymorphisms in the CACNA1S Gene

Abstract: We identified four novel polymorphisms in the CACNA1S gene that encodes the alpha1-subunit of the dihydropyridine receptor. Mutations in this gene are associated with two genetic diseases: malignant hyperthermia and hypokalemic periodic paralysis. The nucleotide substitutions c2403T --> C and c5398T --> C did not result in amino acid replacement, the nucleotide substitution c4475C --> A caused the replacement of the Ala1492 with an Asp residue and an A insertion was identified in intron 36. By using methods ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Cells from CCR5Δ32 heterozygous individuals also show reduced virus entry and infection (45). Human VGCC genes are polymorphic, and there are likely differences in receptor levels among different individuals (47,48). Indeed, mutations in human CACNA1S and CACNA2D2 genes have been linked to several syndromes, and we found that cells from individuals heterozygous for an A1S missense mutation were also less infected by JUNV-C1 (49)(50)(51).…”
Section: Discussionmentioning
confidence: 56%
“…Cells from CCR5Δ32 heterozygous individuals also show reduced virus entry and infection (45). Human VGCC genes are polymorphic, and there are likely differences in receptor levels among different individuals (47,48). Indeed, mutations in human CACNA1S and CACNA2D2 genes have been linked to several syndromes, and we found that cells from individuals heterozygous for an A1S missense mutation were also less infected by JUNV-C1 (49)(50)(51).…”
Section: Discussionmentioning
confidence: 56%
“…The CACNA1S or CACNL1A3, encoding the α1-subunit of the DHPR, is at 1q32 [28]. Polymorphisms and potential mutations have been identified in this gene [30]. In one family, the Arg528His amino acid substitution in the α1-subunit of the DHPR encoded by CACNA1S produced a severe form of hypokalemic periodic paralysis.…”
Section: Other Loci Possibly Associated With Mhmentioning
confidence: 99%